The Effect of Giving Green Spinach Juice on Hemoglobin Levels Among Pregnant Women - Yusra, Yusra; Sutarno, Maryati (STIKep PPNI Jawa Barat, 2024)
Aims: Knowing the effect of giving Green Spinach Juice on Increasing Hemoglobin Levels in Pregnant Women. Methods : A quasi-experimental study design with one group pretest-posttest. In November 2023, 46 pregnant women had their pregnancy checks at PMB Nurida. The sample technique uses the purposive sampling technique. Results : Pregnant women's average hemoglobin level was 9,104 mg/dl before ingesting spinach juice, and 10,770 mg/dl afterward. Giving green spinach juice has a significant effect on boosting hemoglobin levels in pregnant women (p value = 0.000). Conclusions: Increasing the amount of hemoglobin in pregnant women is one of the effects that can be brought about by giving them green spinach juice. For the purpose of preventing anemia during pregnancy, it is planned that midwives will provide counseling to pregnant women, encouraging them to consume vegetables and fruit on a daily basis, particularly those that contain a high amount of iron contents.